PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL: INTEGRASI VARIABEL MEDIASI DAN MODERASI (STUDI PADA RUMAH SAKIT DI KOTA SURABAYA) - WIDYAWATI, NOVI (Jurnal Akuntansi AKUNESA, 2017)
This study examines the effects of budgetary participation to managerial performance with intervening variable: job relevant information. The influences of organization commitment in moderating the relationship of budgetary participation to managerial performance at four hospital in Surabaya. This study uses survey approach with questionnaires as the basis of data retrieval. Based on the test results using WarpPLS 5.0. The result of this study showed that (1) budgetary participation has positive effect to managerial performance, (2) organization commitment moderate the relationship between budgetary participation and managerial performance, (3) job relevant information mediate the relationship between budgetary participation and managerial performance.